Violencia femicida en 2666 de Roberto Bolaño - Ramírez, Susana Florinda (2021)
“La parte de los crímenes”, one of the segments of the novel 2666 (2004) by Roberto Bolaño, narrates in a fictional key, based on journalistic investigations, official records and social organizations, the series of multiple murders of women perpetrated in Ciudad Juárez, Mexico, at the end of the last century and the beginning of the present. The purpose of this article is to inquire into the artistic representation of the extreme violence that attacks without mercy the female bodies in overflowing and irrational way, until forming an apocalyptic vision of the Latin American city. The writing contaminates the testimonial record withfiction to capture feminicide violence, a procedure that eludes the controversial character of the testimony and, instead, concentrates all the power of the story in the exploration of evil in its multiple incarnations. The text combines the parody of the bureaucratic-administrative style with narrative fragments that give voice to the many characters involved in the events. Such a discursive framework sponsors not only the denunciation of these crimes silenced by the authorities but also the inquiry of political, cultural, and economic determinations that converge in the atrocities committed against women. Documents and testimonies are processed on the fictional machine, fusing literature with other narratives that resist the threat of  dehumanization.